Influence of connection stiffness on static-dynamic behavior of steel frames - Bolandim, Emerson Alexandro; Nicoletti, Renato Silva; Rossi, Alexandre; Souza, Alex Sander Clemente de (Acta Scientiarum. Technology, 2022)
The growing problems of excessive vibration in steel structures due to human rhythmic activities and vibrating machinery have led to the need for increasingly rigorous dynamic analysis in order to verify excessive displacements and ensure the users´ comfort. The present work aimed to carry out, via numerical simulation in ANSYS Mechanical APDL software, static, modal and harmonic analysis in steel frames with two floors and two bays in order to investigate the influence of the connection´s stiffness on the behavior of the structure. The results obtained showed that the natural frequency value of the models increases as the stiffness of the beam-column connections is increased. However, due to the harmonic analysis performed, it was not possible to delineate a behavior between the stiffness of the connections and the amplification.